Inn on Mirror Lake - Mason, Debbie (Novelist) (Waterville, Maine Thorndike Press, a part of Gale, a Cengage Company, 2023)
"They swear they're not right for each other but the matchmakers of Highland Falls are out to prove them wrong. Elliana MacLeod has come home to whip the Mirror Lake Inn into tip-top shape, the only way to prevent her mother from selling the beloved family business. In between watching over mischievous, cigar-sneaking Grandpa Joe and trying to help Highland Falls win the Most Romantic Small Town in America contest, Elliana's plate isn't just full, it's overflowing. She can't refuse Nathan Black's offer to fix up the inn, even if the gorgeous law enforcement officer has made it abundantly clear he considers her a friend, and nothing more. Nate knows he's not cut out for long-term relationships or white picket fences, and that's what Ellie deserves. Yet keeping her at arm's length is nearly impossible, especially once they're working--and living--side-by-side. The more time he spends with Ellie, the more he wants, and not just for today but forever. When Ellie's ex returns to town, has Nate missed his chance with the woman of his dreams?"--
111433
Keywords: Hotels -- Maintenance and repair -- Fiction; Family-owned business enterprises -- Fiction; Man-woman relationships -- Fiction; Large type books; North Carolina -- Fiction; Love stories; Large print books; Romance fiction